Introducing the concept of “resource scapes” to account for water, energy and biomass resources’ nexus dependencies and governance - Zeeshan Tahir Virk; Jessica Fennell; Ali Torabi Haghighi; Bjorn Klove (Resources, Environment and Sustainability)
Existing methods for resource nexus analysis do not cover all aspects of complex resource management problems. Key methodological challenges include setting the scale, scope, and resolution of a nexus analysis, as well as adequately representing the quantity and quality of resource interactions. Additionally, determining the degree of collaborative governance for resource management, accounting for the role of existing policies, and developing robust scenarios for future predictions are also crucial constraints. To address these limitations, we developed a conceptual model of the resources nexus for Otta valley in Norway, an area characterized by resource use trade-offs across interconnected systems. We introduced the concept of “resource scapes” which is the physical availability, key interactions, management networks, and policies governing a resource at a specific time and place. We defined resource scapes for water, energy, and biomass resources in the studied area. Employing stock and flow loops, social network analysis, material flow accounting, and policy reviews, we developed the model in a layered topology using the coupled component modeling approach. In addition, we developed future resource scenarios nested within national pathways – the Norwegian nexus pathways (NNPs) – aligned with the five globally adopted shared-socioeconomic pathways (SSPs), using a narrative downscaling approach. Our results show that annual variations in resource balances are connected to changing externalities. A low Network External-Internal (EI) index (0.392) indicates weak overall collaborative governance of nexus resources. Our modeling framework (1) addresses limitations in current nexus methods, (2) facilitates testing of alternative policy interventions under future scenarios, and (3) provides a framework for development of integrated assessment models. This approach merges the concept of nexus governance with integrated assessment modeling, thereby enhancing the application of nexus approach for efficient resource management which will be crucial in future as climate and socioeconomic conditions evolve.